A Short Glance on Public Enterprises in Nepal - Sharma, Ajita Devi (Academic View, Journal of TUTA Tri-Chandra Campus Unit, 2023)
This article deals with Public Enterprises, types, performances, and its reflections on the Nepalese context. Public Enterprises are entities with specific objectives involving government ownership and control through public authority. PEs have been established in Nepal for economic and balanced development through performing specific business functions. This article claims that the number of PEs grew from the period of Nepal’s first five-year plan, which was reduced after adopting liberalization and privatization policy in the era of multiparty democracy. The main objective of this article is to trace out the scenarios of Public Enterprises, its challenges and their opportunities. It has applied the review-based analysis as a methodological part. Most PEs are running under huge losses, very few have operating excellent performances and public notice. The major challenges for PEs in Nepal are heavy political interference, government and remuneration policy, lack of transparency and accountability, low commercial expertise, and nepotism with bureaucratic organizational structure. The PEs are a tool for implementing government policy as well as an agent for market control and competition in a positive aspect. Improvement in the fundamentals of PEs is necessary for them to sustain in a competitive market and be serviceable to society. Efficiency-based remuneration and recognition motivate the individual to take risks and contribute to the national economy.